International Education beyond State Regulations in Indonesia: Practices from Y Province-Based Public and Private High Schools - Junita Widiati Arfani (Policy & Governance Review, 2019)
The objective of this study is to examine implementation of the international education (IE) policy (under the so-called Undang-Undang Sistem Pendidikan Nasional (the Law of National Education System) and its legal derivatives) at high school level in Indonesia by investigating the policy text and its dynamic practices concerning the IE policies at both public and private schools. The study employs qualitative case study methodology combining data collection methods which include individual interviews to key resource persons and documents analysis at national, local and at school levels. Using the Vidovich policy framework, the study explores how national executive, legislative and judicial (states) bodies interact in formulating IE policy and how the policy has impacted at school level. Two schools of public and private that implemented international curriculum were selected as case studies. The study finds that the IE policy that was initially formulated at national level by relevant state authorities/agencies has however resulted in weakening role of the state due in part to its centralized feature (despite its decentralized implementation claim). Consequently, in the stage of its implementation at school level, providers of IE and their champions as non-state actors play significant roles. The study indicates importance and significance of relevant state authorities at local government level in the framework to offer effective supervision on the IE policy implementation.